PENERAPAN ARSITEKTUR EKOLOGIS PADA STRATEGI PERANCANGAN SEKOLAH MENENGAH KEJURUAN PERTANIAN DI SLEMAN - Amalia Dian Utami; Sri Yuliani; Ummul Mustaqimah (Universitas Sebelas Maret Surakarta, 2017)
The design of Sleman Agricultural Vocational High School (SMK Pertanian Sleman) with the approach of ecological architecture is motivated by three things : the existence of agricultural potential in Sleman, the prospect of Agricultural Vocational School in Sleman, and the need to apply ecological architecture on buildings constructed in predominantly agricultural area. SMK Pertanian Sleman aims to educate the community in the surrounding area, create innovations, and aplace to learn modern agriculture. The method used is architectural design that combines the ecological architecture essence according to Heinz Frick, Wanda Widigdo, and V.A. Metallinaou which is combined with ecological architectural components according to Ken Yeang. The result is the design of educational facility which includesclassrooms, laboratories, mini market where students can sell their agricultre product, and other support rooms. Keywords: school of agriculture, ecological architecture, Sleman